Health Services Research Evaluation Principles - Sockolow, P. S.; Crawford, P. R.; Lehmann, H. P. (Methods of Information in Medicine, 2012)
Background: Our forthcoming national experiment in increased health information technology (HIT) adoption funded by the American Recovery and Reinvestment Act of 2009 will require a comprehensive approach to evaluating HIT. The quality of evaluation studies of HIT to date reveals a need for broader evaluation frameworks that limits the generalizability of findings and the depth of lessons learned.Objective: Develop an informatics evaluation framework for health information technology (HIT) integrating components of health services research (HSR) evaluation and informatics evaluation to address identified shortcomings in available HIT evaluation frameworks.Method: A systematic literature review updated and expanded the exhaustive review by Ammenwerth and deKeizer (AdK). From retained studies, criteria were elicited and organized into classes within a framework. The resulting Health Information Technology Research-based Evaluation Framework (HITREF) was used to guide clinician satisfaction survey construction, multi-dimensional analysis of data, and interpretation of findings in an evaluation of a vanguard community health care EHR.Results: The updated review identified 128 electronic health record (EHR) evaluation studies and seven evaluation criteria not in AdK: EHR Selection/Development/Training; Patient Privacy Concerns; Unintended Consequences/ Benefits; Functionality; Patient Satisfaction with EHR; Barriers/Facilitators to Adoption; and Patient Satisfaction with Care. HITREF was used productively and was a complete evaluation framework which included all themes that emerged.Conclusions: We can recommend to future EHR evaluators that they consider adding a complete, research-based HIT evaluation framework, such as HITREF, to their evaluation tools suite to monitor HIT challenges as the federal government strives to increase HIT adoption.
Keywords: Evaluation studies; technology evaluation; health information systems; medical informatics; review